A survey of the conservation programs and practices on special collections and archival materials in the University of the Philippines Diliman libraries - Rebolledo, Anthony J.; Granda, Yolanda C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1998)
The study is intended primarily to find out the conservation program, practices, conditions, problems and existence of the conservation of special collections and archival materials in the University of the Philippines Diliman libraries and to propose necessary measures towards the improvements. It was carried out in response to the expressed need of librarians and archivists that the development of a comprehensive library and archives requires, among others the support of an efficient and cost effective conservation program.
The institutions covered in the study include a total of thirty (30) unit libraries and archives, including several sections in the Main Library. These include institutions which have conservation programs and all units which do not have such programs but are interested in developing one. Two libraries, which are under the control of the U.P. Diliman Library System, are not part of this study for reasons of proximity. The respondents of this study include head librarians and chief archivists of the institutions.
The descriptive sample survey method of research design is employed as research methodology. Questionnaires, interviews, visits, observations, and analysis of documentary sources are employed to gather data for the study. The resulting questionnaires are divided into four parts. Data from accomplished questionnaires are compiled, classified, and tabulated by the researcher. Responses are analyzed by frequency distribution because of the small number of respondents. Rank order is computed to determine common concerns on problems and needs encountered in conserving collections.
The research findings showed that: 1) Special collections and archival materials were present in the institutions surveyed. The special collections consist of: a) rare/vernacular/unique books and serials; and b) manuscript, artifacts, and other non-book collections. The archival materials are classified according to their importance to either the college or the university. These are composed of different record series, such as theses and dissertations of respective students, minutes of meetings, and memorabilia among others; 2) The conservation activities of the institutions surveyed, which are geared toward methods that prevent, deter, or halt the deterioration of materials, consist of such measures as cleaning, encapsulation, photocopying, document imaging, classical binding, and fumigation. The conservation activities adapted by some of the respondent institutions which are geared towards the restoration of altered collections consist of cleaning with organic solvents, fumigation, washing, deacidification, bleaching, stabilization and lamination; 3) As indicated by the efforts exerted by respondent institutions in conserving their special collections and archival materials, a lack of enthusiasm pervades. In conserving the general collection, however, a general awareness of the problem exists. Nevertheless, there are still a lot of improvements yet to be initiated and maintained.
Conclusions drawn from the study include the following: 1) There is a lack of awareness in the deterioration of the special collections and archival materials because of the insufficient effort and enthusiasm to preserve and restore these materials. However, as indicated by the existence of conservation techniques for the general collection in almost all the institutions surveyed, general awareness of the problem of deterioration in the general collection pervades; and 2) The need to conserve special collections and archival materials is given a lesser degree of importance when compared to the conservation of the general collection.
In the light of the foregoing study, this research study recommends the following: 1) The presentation of a convincing and justifiable proposal on the importance of a conservation program in order to obtain management support; 2) The immediate planning and careful implementation of a conservation program for each institution to be able to preserve and restore special collections and archival materials; 3) The formulation of a written conservation policy to guide the implementation of the program; 5) The development of a conservation training program to orient and train the conservation staff on the practical and scientific approaches to conservation; 6) The formation of a "conservation consortium" to be encouraged by libraries and archives to better carry out definite conservation projects, such as training provisions and acquisition and maintenance of valuable but costly supplies and equipment; 7) The inclusion of a conservation course to the library science curriculum to properly train and fully prepare library science graduates in the conservation of collections.
Vita.
Computer print out.
Thesis (Bachelor of Library and Information Science)
Keywords: Libraries -- Special collections -- Conservation and restoration; Archival materials -- Philippines -- Quezon City -- Conservation and restoration; University of the Philippines (Diliman). Libraries